Opening Up the Sea: A Novel Methodological Approach to Display Mediterranean Shoreline Evolution - Augusto Palombini; Giulio Lucarini; Paolo Rosati; Crescenzo Violante (Proceedings)
This paper presents a methodological proposal in order to use marine geology data on sea level change through time, to reach an effective display of shoreline evolution in a form easily suitable by archaeologists, taking into account the need of reliable DEMs and hypothetical ancient sea surfaces. The technical aspects and steps of the process are explained, so as to present a possible approach proposal for any area or chronological phase exclusively on the basis of open source software and freely available data.